Perancangan Sistem Informasi Pemesanan Menu Berbasis Android - Chaeroen Niesa; Mutasar Mutasar; Uswatul Hasanah (Jurnal Tika, 2023)
MC Coffe Bireuen is a place visited by customers to shop for food and drinks, the restaurant business has been very much in demand by the public in general, because apart from having a good turnover, it is also easy to develop. The current condition at MC cafe is still using the manual ordering method and the exemption from the use of internet access by customers. This makes it difficult for cafe owners to spend on internet access bills, plus the payment system is still manual which causes the calculations to be quite time consuming. then designed a local website and management system for the use of internet access that is able to provide solutions in working on ordering services. In the design of this application system, it provides an Android ordering menu to make it easier for customers and their workers to handle orders and payments.